Experimental Study on Monitoring Equipment for the Scouring and Sedimentation of Wharf Bank Slopes Based on Heat Transfer Principles - Jilong Yin; Huaqing Zhang; Mengmeng Liu; Qian Ma (Sensors)
The scouring and sedimentation of wharf bank slopes significantly impact port safety and efficiency. To overcome the limitations of existing monitoring technologies in real-time capability, adaptability, and precision, this study introduces an innovative device based on distributed fiber optic sensing technology. By analyzing changes in the temperature gradient at the water–soil interface, the device enables dynamic monitoring of the results of scouring and sedimentation processes. It employs a modular design, integrating a linear heat source with fiber optic temperature sensing to capture high-resolution changes. Laboratory experiments evaluated variables such as heating duration, pipe material, pipe diameter, and fiber winding pitch. Results show optimal performance with a 20-min heating duration, with PVC sensors offering higher sensitivity and steel sensors providing greater stability. This study presents a high-precision, real-time solution for monitoring wharf bank slopes, offering insights for equipment optimization and engineering applications.